Особенности организации тканевого метаболизма у двустворчатого моллюска-вселенца Anadara inaequivalvis Bruguiere - Солдатов, А.А.; Андреенко, Т.И.; Головина, И.В. (Видавничий дім "Академперіодика" НАН України, 2008)
Peculiarities of the glucose and protein metabolisms in tissues of Black Sea bivalve mollusks: Anadara inaequivalvis Bruguiere (invader) и Mytilus galloprovincialis Lam. (mass species) are compared. It is marked that the metabolism organization in A. inaequivalvis organism has expressed a tissue specificity. Anaerobic processes predominated in gills and digestive gland of mollusk under external normoxia conditions. The highest activities of malate and lactate dehydrogenases against the background of a higher content of lactate and a decreased glucose concentration in tissues testify to this. Simultaneously, the active protein degradation in gills and digestive gland of A. inaequivalvis is marked. Free aminoacid pool, aminoacid/protein index, and urea tissue level were higher than those in M. galloprovincialis. On the contrary, the foot metabolism of A. inaequivalvis was oriented to aerobic processes. The role of environmental conditions and mollusk’s behavior in the tissue metabolism organization of this species are considered.